MASTECTOMY: SCARS IN FEMALE SEXUALITY. - Durães Rocha, Jucimere Fagundes; Rodrigues Cruz, Priscila Karolline; Aparecida Vieira, Maria; Marques da Costa, Fernanda; de Almeida Lima, Cássio (Journal of Nursing UFPE / Revista de Enfermagem UFPE)
Objective: to describe the reflexes of the mastectomy on the women´s sexuality attended in the Women´s Health Program. Method: it is a descriptive, qualitative study with 14 women submitted to total mastectomy in Montes Claros/MG. The data collection was performed through the semi-structured individual interview; then the analysis was performed from the Content Analysis Technique. Results: three categories were defined << Experiencing breast cancer: the reconstruction of the female identity after mastectomy >>; << Mastectomy and sexuality in times of cult of the body: implications in the sense of the female body >>; << When the mastectomy transcends the body: the scars on sexuality >>. Women with mastectomy experience feelings such as despair, sadness, and loss, but begin to construct a new definition of woman. Conclusion: the mastectomy experience is diverse and different for each woman, involving implications on identity, body, and sexuality.